Economic valuation of farmland using natural-attribute–based indicators: A case study of Hefei, China - Li Yuan; Xun Fan; Binrui Feng (PLoS ONE, 2025)
The economic valuation of farmland traditionally focuses on market-based approaches, potentially undervaluing the fundamental role of natural attributes. This study aims to assess the economic value of farmland by explicitly integrating key natural attributes, including soil fertility, slope, and climatic conditions. This study develops a novel assessment framework integrating natural attributes to determine farmland economic value, with Hefei, China as the case study. The assessment combines three methods: the Comprehensive Farmland Quality Index to classify farmland by quality, the Thornthwaite-Mather model to estimate effective precipitation and water availability, and the soil productivity potential method to calculate baseline productive capacity. Together, these methods provide an objective, reproducible, and ecologically grounded basis for farmland valuation. The results reveal the economic value of farmland in Hefei. Key findings include: In 2021, the total area of farmland in Hefei was 481,500 hectares, with approximately 5% classified as first-grade land, 10% as second-grade land, 19% as third-grade land, 32% as fourth-grade land, and 33% as fifth-grade land. The estimated standard production potential per unit of farmland in 2021, from highest to lowest, was 10.28 t·hm −2 , 9.94 t·hm −2 , 9.31 t·hm −2 , 8.91 t·hm −2 , and 7.95 t·hm −2 for first- to fifth-grade land, respectively. Based on rice production inputs and outputs, the estimated economic value reflects a single-year, non-discounted theoretical output. The economic total value of farmland in Hefei in 2021 was calculated to be 1.363 billion yuan. Specifically, the economic value of first-grade farmland was 81 million yuan; second-grade farmland was 158 million yuan; third-grade farmland was 273 million yuan; fourth-grade farmland was 444 million yuan; and fifth-grade farmland was 407 million yuan. Among all districts of Hefei, the economic value of farmland in 2021 ranked from highest to lowest as follows: Chaohu, Feidong, Feixi, Lujiang, Shushan, Yaohai, Luyang, and Baohe.